Research on deep hole convergence energy blasting for increasing permeability in deep wells with high gas and low permeability coal seams - Shigui FU; Zegong LIU; Shuai CHANG; Shuai YANG; Jianyu ZHANG; Guodong QIAO; Xin ZHANG (Meitan kexue jishu)
With the gradual deepening of coal mining, the issue of high ground stress will be faced. In response to the unclear understanding of the internal damage and fracture evolution of deep wells with high gas and low permeability coal seams under the influence of deep ground stress, a theoretical model of convergence energy blasting jet formation was established. The critical collapse velocity of the convergence jet formation was studied, verifying the feasibility of jet formation, and analyzing the mechanism of convergence energy blasting load erosion on coal seams. Subsequently, through laboratory experiments, comparative simulations of convergence energy blasting and conventional blasting at different burial depths were conducted, analyzing the effects of convergence energy blasting and conventional blasting on coal seam crack propagation from three aspects: macroscopic cracks, strain conditions, and ultrasonic data. Then, numerical simulation software was used to study the distribution characteristics of coal damage under convergence energy blasting loads at different burial depths. Finally, the effects of normal blasting and convergence energy blasting under different buried depths on gas concentration and gas extraction purity are studied through field tests. The results of blasting similarity simulation experiments show that deep ground stress can inhibit the fracturing range of blasting loads on coal bodies, and conventional blasting is more affected by ground stress than convergence energy blasting. Relative to conventional blasting, the fracturing range of convergence energy explosives in deep coal bodies is wider during permeability enhancement blasting. The maximum pressure strain peak at measurement point 1# in the convergence direction is 1.35 times that of conventional blasting, while at measurement point 3# in the non-convergence direction, it is 86% of conventional blasting. This also results in cracks preferentially propagating in the convergence direction, with less expansion in the non-convergence direction, leading to better directional blasting effects. Numerical simulation results indicate that with increasing burial depth, the range of coal penetration by convergence energy blasting decreases. A relationship formula between different burial depths and the fracturing range of convergence energy blasting was fitted, which can serve as a basis for determining the fracturing range of deep mine convergence energy blasting to some extent. Field test results show that deep hole convergence energy blasting can increase gas extraction to a greater extent than common deep hole blasting. The buried depth has a certain influence on the crack range of deep hole convergence energy blasting, so the influence of ground stress should be considered when using shaped charge blasting in deep mine. The research findings have certain reference significance for the blasting permeability enhancement of deep high gas and low permeability coal seams.